Conditional knockout of hephaestin in the neural retina disrupts retinal iron homeostasis - Zhang, Kevin R; Baumann, Bailey; Song, Ying; Sterling, Jacob; Erler, Elizabeth A; Guttha, Samyuktha; Kozmik, Zbynek; Dunaief, Joshua L (Experimental eye research, 2022)
Iron accumulation has been implicated in degenerative retinal diseases. It can catalyze the production of damaging reactive oxygen species. Previous work has demonstrated iron accumulation in multiple retinal diseases, including age-related macular degeneration and diabetic retinopathy. In mice, systemic knockout of the ferroxidases ceruloplasmin (Cp) and hephaestin (Heph), which oxidize iron, results in retinal iron accumulation and iron-induced degeneration. To determine the role of Heph in the retina, we generated a neural retina-specific Heph knockout on a background of systemic Cp knockout. This resulted in elevated neural retina iron. Conversely, retinal ganglion cells had elevated transferrin receptor and decreased ferritin, suggesting diminished iron levels. The retinal degeneration observed in systemic Cp-/-, Heph-/- mice did not occur. These findings indicate that Heph has a local role in regulating neural retina iron homeostasis, but also suggest that preserved Heph function in either the RPE or systemically mitigates the degeneration phenotype observed in the systemic Cp-/-, Heph-/- mice.
Keywords: Iron; Ferrous; homeostáza; Animals; retina; ceruloplasmin; Age-related macular degeneration; Mice; Hephaestin; Retina; Macular Degeneration; železo; Membrane Proteins; makulární degenerace; zvířata; membránové proteiny; myši knockoutované; Homeostasis; Mice, Knockout; myši; Ceruloplasmin